2018
DOI: 10.1111/gbb.12542
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for lack of direct causality between pain and affective disturbances in a rat peripheral neuropathy model

Abstract: Chronic pain is frequently accompanied by the manifestation of emotional disturbances and cognitive deficits. While a causality relation between pain and emotional/cognitive disturbances is generally assumed, several observations suggest a temporal dissociation and independent mechanisms. We therefore studied Sprague‐Dawley rats that presented a natural resistance to pain manifestation in a neuropathy model (spared nerve injury [SNI]) and compared their performance in a battery of behavioral paradigms—anxiety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 78 publications
(172 reference statements)
1
19
0
1
Order By: Relevance
“…Moreover, similarly to WKY rats, LEW rats have been suggested as a high-anxiety counterpart to the SHR strain when modeling high and low indices of basal anxiety 21,86,87 . Despite detecting very prominent differences in evoked pain-like behaviour between strains, we did not see any correlation between magnitude of neuropathic pain-like behaviour and affective changes indicative of the presence of anxiety-or depressive-like behaviour, confirming other recent findings 33,88 . Notably, the only strain showing anxiety-like behaviour in the EPM following nerve injury was the moderately pain-sensitive F344/DU.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, similarly to WKY rats, LEW rats have been suggested as a high-anxiety counterpart to the SHR strain when modeling high and low indices of basal anxiety 21,86,87 . Despite detecting very prominent differences in evoked pain-like behaviour between strains, we did not see any correlation between magnitude of neuropathic pain-like behaviour and affective changes indicative of the presence of anxiety-or depressive-like behaviour, confirming other recent findings 33,88 . Notably, the only strain showing anxiety-like behaviour in the EPM following nerve injury was the moderately pain-sensitive F344/DU.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, animals with or without anxiety‐ and/or depression‐like phenotype can show similar mechanical or thermal withdrawal thresholds in animal models of pain (Gui et al, 2016; Xie et al, 2017; Yang, Fang, et al, 2019). Conversely, a recent study showed that rats that do not develop mechanical allodynia after SNI can still develop anxiodepressive‐like behaviours similarly to painful rats (Guimaraes et al, 2019). There is thus no correlation in rodent models of chronic pain between the nociceptive response and the development of anxiodepressive disorders, which is similar to clinical reports (Bagnato et al, 2015; Dickens, Jayson, & Creed, 2002; Jensen et al, 2010; Keltner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, a causal link between pain and anxiodepressive consequences should not necessarily imply direct correlation between the intensity of nociceptive and anxiodepressive symptoms. Some observations suggest a temporal dissociation and partly independent mechanisms between these aspects of chronic pain (Gui et al, 2016; Guimaraes et al, 2019; Zhou et al, 2015). As example, in a model of sciatic nerve compression, mechanical hypersensitivity is no longer present 2–3 months after the surgery, while anxiodepressive‐like behaviours can persist after the recovery of hypersensitivity (Dimitrov et al, 2014; Sellmeijer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical allodynia was assessed as previously described (Guimarães et al, 2018) using the up-and-down method (Chaplan et al, 1994). Briefly, Von Frey monofilaments of different forces were used: 15.0 g, 8.0 g, 6.0 g, 4.0 g, 2.0 g, 1.0 g, 0.6 g and 0.4 g (North Coast Medical Inc., USA).…”
Section: Methodsmentioning
confidence: 99%